Deleuze and becoming-citizen: Exploring newcomer films in a Franco-Canadian secondary school. Issue 1 (1st December 2014) - Bangou, Francis; Fleming, Douglas
Citizenship and citizenship education have been traditionally bounded to either a geographically bound nation-state or a historically shared culture. In this article we argue that it is no longer enough to explore the complexity of what we term becoming-citizen in today's information-based society where multiple national and cultural connections and affiliations are a mouse click away. We make the case for the importance of understanding how developing literacies affect how citizenship is transformed in pedagogical settings, particularly in terms of how Information and Communication technologies (ICT), the curriculum and teaching intersect and affect each other as complex systems. To do this, we use Deleuze and Guattari's concept of agencement and Multiple Literacies Theory (MLT) to map how citizenship emerges in a group of young newcomer students' texts (broadly defined) as filmed with pocket size digital video cameras. The research reported here comprises part of a three-year research project on the interrelationships between citizenship, technology and pop culture in a French secondary inner-city Ottawa schools. We begin with an outline of the concepts of agencement and MLT. We then briefly summarize the current literature on citizenship education before proceeding to an account of how our research has been guided by rhizoanalysis. We then proceed to three vignettes associated with the curriculum used in the particular school under study and two video clips shot by two newcomer students. We conclude with a discussion of the implications of our study in terms of theory and practice.